Electrochemical conversion of corn stover lignin to biomass-based chemicals between Cu/NiMoCo cathode and Pb/PbO2 anode in alkali solution. (20th February 2018) - Cai, Pan; Fan, Hongxian; Cao, Shuo; Qi, Jian; Zhang, Songmei; Li, Gang
Abstract: In this study, we put forward an effective method of producing renewable chemicals from corn stover lignin with electrochemical redox between the Cu/NiMoCo cathode and Pb/PbO2 anode in sodium hydroxide solution. Cyclic voltammetry tests and polarization curves were conducted to research the electrochemical oxidation performance of Pb/PbO2 anode and electrocatalytic hydrogenation of Cu/NiMoCo in lignin alkali solution. Fourier transform infrared spectroscopy (FTIR) and high performance liquid chromatography (HPLC) were used to characterize the functional groups and molecular weight distribution of the lignin residue. By GC-MS analysis, it confirmed that there were 24 kinds of compounds in degradation products of alkali corn stover lignin. In addition to this, some commercial value chemicals including trans-ferulic acid, vanillin, 3-hydroxy-4-methoxyphenyl-ethanone, syringaldehyde, acetosyringone and 4-methoxy-3-methyl-phenol were also observed. Graphical abstract: Highlights: An electrochemical redox process for conversion of corn stover lignin into biomass-based chemicals. Cracking lignin by electrochemical oxidation of Pb/PbO2 anode. Hydrogenating lignin intermediates by electrocatalytic reduction of Cu/NiMoCo cathode.